The effects of an apology’s timing and type on parole board decision-making - Cunius, M. Katie (Criminal justice studies, 2023)
There are various psychological factors that could impact a parole member’s decision, including whether the prisoner apologizes. This study investigates the effects of an apology’s type and timing on parole members’ release decisions. MTurk participants (N = 460) read vignettes describing a prisoner whose apology differed in its timing (at trial, parole hearing, or both) and type (full, partial). An apology at both the trial and parole hearing is the most effective apology, and a partial parole apology is the least effective apology. This apology also affects the parole member’s perception of the prisoner. Further, male participants (compared to female participants) are more empathetic toward, more likely to feel sorry for, and more likely to perceive similarities with the prisoner. These findings can help the legal system understand how apologies affect parole members’ decisions, and how to create laws that can systematically allow apologies to be considered in parole releases.